Proton beam therapy achieves excellent local control for recurrent epithelial ovarian cancer: a single-center retrospective study - Yuta Endo; Yoshiaki Takagawa; Yuki Yoshimoto; Masanori Machida; Yuntao Dai; Yusuke Azami; Ichiro Seto; Kanako Takayama; Motohisa Suzuki; Tatsuhiko Nakasato; Yasuhiro Kikuchi; Takahiro Kato; et al. (Journal of Ovarian Research)
Abstract Background Previous studies have demonstrated the benefit of radiation therapy for patients with recurrent epithelial ovarian cancer; however, the effects of proton beam therapy in these patients remain unelucidated. This study aimed to evaluate the use of proton beam therapy in recurrent epithelial ovarian cancer and to identify factors predictive of local control. Results This retrospective study included 13 patients with a total of 30 lesions who underwent proton beam therapy for recurrent epithelial ovarian cancer at our institution between October 2008 and March 2021. The median age of the patients at the initial proton beam therapy was 62 (range, 42–82) years. Eight patients had stage III or IV disease, and seven had serous carcinoma; ten patients exhibited platinum resistance. The irradiated sites included 16 lymph nodes and 9 pelvic or abdominal masses. The median tumor size and maximum standardized uptake value (SUVmax) of fluorine-18-fluorodeoxyglucose-positron emission tomography/computed tomography (18F-FDG-PET/CT) were 25 (range, 9–83) mm and 12.6 (range, 3.9–25.1), respectively. The median total dose was 65 (range, 45–72) Gy (relative biological effectiveness). The 1- and 2-year local control were 91.5% and 71.3%, respectively. The SUVmax of 18F-FDG-PET/CT was a significant predictor of local control (cutoff value, 17.7). The median progressing-free and overall survival after proton beam therapy initiation were 9.6 and 21.5 months, respectively. No grade 3 or higher proton beam therapy-induced adverse events were observed. Conclusion Proton beam therapy demonstrated excellent local control of recurrent epithelial ovarian cancer, with tolerable toxicity, suggesting that this modality may represent a promising treatment option. The SUVmax of 18F-FDG-PET/CT performed prior to proton beam therapy may serve as a predictor of local control. Clinical trial number Not applicable.